Правові основи податкової системи України: сучасний стан, основні елементи, принципи - Барін, Олександр (My University, 2018)
Дисертація є одним із перших у вітчизняній фінансово-правовій літературі монографічних наукових досліджень, в якому, зважаючи на євроінтеграційні процеси та кризовий стан держави, розглянуто теоретичні та практичні проблеми правових основ податкової системи у сучасних умовах. Досліджено загальні положення про податкову систему у правовому вимірові, проаналізовано принципи як засадничі елементи податкової системи, розглянуто податковий обов’язок та податкову правосуб’єктність як суб’єктні елементи податкової системи. Удосконалено визначення понять «податкова система», «система оподаткування», «принцип податкової соціальної справедливості», «принцип ефективності оподаткування», «податкова правосуб’єктність», «податкове зобов’язання», «податковий обов’язок» тощо. Досліджено різні моделі податкової політики, розглянуто принципи податкової політики, досліджено стадії та методи податкової політики.

Диссертация является одним из первых в отечественной финансово- правовой литературе монографических научных исследований, в котором, учитывая евроинтеграционные процессы и кризисное состояние государства, рассмотрены теоретические и практические проблемы правовых основ налоговой системы в современных условиях. Исследованы общие положения о налоговой системе в правовом измерении, проанализированы принципы как основные элементы налоговой системы, рассмотрены налоговая обязанность и налоговая правосубъектность как субъектные элементы налоговой системы. Аргументировано, что налоговая система включает: базовые принципы налогообложения; систему налогов и сборов; налоговую правосубъектность (права, обязанности, ответственность участников налоговых отношений и порядок их реализации); налоговую обязанность (порядок начисления, удержания, уплаты или взыскания и перечисления налогов и сборов). Администрирование налогов и сборов как управленческая деятельность контролирующих органов (фискальных органов) в сфере налогообложения является сквозным элементом налоговой системы, поскольку в той или иной мере элементы системы администрирования касаются тех или иных элементов налоговой системы. Усовершенствованы определения понятий «налоговая система», «система налогообложения», «принцип налоговой социальной справедливости», «принцип эффективности налогообложения», «налоговая правосубъектность», «налоговое обязательство», «налоговая обязанность» и другие. Рассмотрены различные модели налоговой политики, выделены принципы налоговой политики, исследованы стадии и методы налоговой политики.

The dissertation is one of the first researches done in financial and legal literature of monographic study in Ukraine which envisages theoretical and practical problems of legal foundations of tax system nowadays taking into account the Euro integration processes and crisis state of the state. The general provisions of the tax system in legal dimension have been studied, the principles as the basic elements of the tax system have been analyzed, the tax obligation and tax legal personality as subject elements of the tax system have been considered. It has been stated that a tax system embraces the basic principles of taxation, the system of taxes and levies; the tax legal personality (rights, duties, responsibility of tax relation participants and the mechanism of their realization); tax obligation (surcharges, deduction, payment or penalties and remittance of taxes and levies). The administration of taxes and levies as a management activity of control bodies (fiscal bodies) in the sphere of taxation is a vital element of the tax system as this way or another the elements of the administration system concern the appropriate elements of the tax system. It has been suggested to divide all the elements of the tax system into fundamental elements (here we speak of the principles of taxation, tax system, tax law) and subjective elements (include tax duty, tax lagal personality). The objects, basis, period of taxation etc. are the elements of taxation law which are, in this way or another, under the cover of the above said fundamental and subjective elements of the tax system. The civilized system of taxation has been rejected as various formations appear on the political map of the world claiming to be “civilized”. They enjoy all modern economical, technical, and cultural benefits; their people consider themselves culturally developed whereas the world community does not recognize such formations as legal ones. Due to this the term “civilized” is not worth application as for taxation. The taxation process is suggested to be considered as having the following stages: establishing taxes and levies, tax and levies collection, control, and responsibility. Any process has its stages and law users should know what this or that stage means. The definitions of some notions such as “taxation system”, “principle of tax social justice”, “principle of taxation effectiveness”, “tax legal personality”, “tax obligation”, “tax duty” have been specified. Some reconsidered definitions are suggested to make legal terms in Tax Code of Ukraine. Various models of tax policy have been studied. It has been emphasized that the model of tax policy known as the model of “maximum taxes” in democratic law-abiding states is quite problematic as such measures inevitably result in tax-payers dissatisfaction, shadow economy increase, capital outflow etc. The model of minimum tax policy is the most optimal for tax payers (especially as compared to the previous one). At the same time such a model is not beneficial for the state. The model of the policy of “reasonable” taxes is a certain compromise between the above mentioned two models. The principles of tax policy have been considered. The stages and methods of tax policy have been investigated. It has been established that a state tax policy includes the following measures: development of the strategy and the appropriate theory of tax system development with all necessary calculations made, determination of directions, principles and mechanism of taxation, elaboration of measures aimed at achieving the goals set in economic, political, and social spheres of the state development. The changes and amendments have been offered to Tax Code of Ukraine in the part of determining the tax elements, physical entities taxation as well as the definition of the notions “tax obligation”, “money obligation” etc.
дис. ... к.ю.н. : 12.00.07
Барін О.Р. Правові основи податкової системи України: сучасний стан, основні елементи, принципи: дис. … канд. юрид. наук. Одеса, 2018. 193 с.
Keywords: податки; податкова система; принципи оподаткування; податковий обов’язок; податкова правосуб’єктність; податкова діяльність держави; податкова політика; налоги; налоговая система; принципы налогообложения; налоговая обязанность; налоговая правосубъектность; налоговая деятельность государства; налоговая политика; taxes; tax system; taxation; principles fundamentals; tax legal personality; state tax activity; tax policy